2021
DOI: 10.2147/jhc.s316117
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Hepatocellular Carcinoma Response to Transcatheter Arterial Chemoembolization: A Real-World Study Based on Non-Contrast Computed Tomography Radiomics and General Image Features

Abstract: To construct a predictive model of short-term response and overall survival for transcatheter arterial chemoembolization (TACE) treatment in hepatocellular carcinoma (HCC) patients based on non-contrast computed tomography (NC-CT) radiomics and clinical features. Methods: Ninety-four HCC patients who underwent CT scanning 1 week before the first TACE treatment were retrospectively recruited and divided randomly into a training group (n = 47) and a validation group (n = 47). NC-CT radiomics data were extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…This was likely attributable to suboptimal organ segmentation in non-contrast CT. This contrasts with a recent study in which a combination of non-contrast CT radiomics and clinical variables proved to be effective in predicting overall survival (OS) in HCC patients following TACE 41 .…”
Section: Discussionmentioning
confidence: 57%
“…This was likely attributable to suboptimal organ segmentation in non-contrast CT. This contrasts with a recent study in which a combination of non-contrast CT radiomics and clinical variables proved to be effective in predicting overall survival (OS) in HCC patients following TACE 41 .…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have shown that radiomics models with or without clinical factors had good performance in predicting the first TACE response in patients with HCC (AUC 0.815-0.900) [ 26 28 ]. We assessed the treatment response at 6 months, which possessed more clinical value than that after the first treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent report used MRI radiomics nomogram to predict recurrence after ablation at 1, 2, and 3 years in HCC patients, the AUCs of which (0.72, 0.61 and 0.64) were lower than our study (0.867) [ 29 ]. Moreover, most published studies used CT-based radiomics [ 21 , 22 , 24 , 26 28 , 30 ], but MRI is known to have higher soft-tissue contrast than CT and is more commonly used in treated HCC viability evaluation. Based on the reports that postoperative CT and MRI were of predictive value for outcome of LRT [ 23 25 ], our study used initial postoperative MRI.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies have been published using texture analysis or radiomic techniques to predict the response of TACE in HCC across different modalities, such as non-contrast CT [21], contrast CT [22], and MRI [23], with good performance (AUC ranging from 0.884-0.960). Tumor heterogeneity and size were identi ed as critical prognostic features in the Nested multiparametric decision tree [24].…”
Section: Discussionmentioning
confidence: 99%